Comparison of vacuum metal deposition and 1,2-indandione/ninhydrin reagent method for the development of fingerprints on renminbi - Cong Wang; Zunlei Qian; Wei Li; Yaping Luo (Wolters Kluwer Medknow Publications, 2017)
It is extremely difficult to develop fingerprints from the surface of currency. There are studies reporting that the high vacuum metal deposition (VMD) method can be used to detect fingerprints on certain types of currency notes. Both VMD and 1,2-indandione/ninhydrin techniques are employed to visualize latent fingermarks on porous surfaces, such as paper. The current study explores whether the VMD method or 1,2-indandione/ninhydrin reagent method is more effective in the development of fingerprints on renminbi (RMB). Uncirculated, circulated, and water-exposed RMB was utilized in this study, along with five donors who ranged in their age and potential to leave fingermarks. Samples were aged for a determined period (for uncirculated and circulated RMB, times were 1, 3, 5, 10, and 35 days; for water-exposed RMB, exposure time was 1 day) and then treated with VMD and 1,2-indandione/ninhydrin. The results suggested that the 1,2-indandione/ninhydrin reagent yielded a better effect for both circulated and uncirculated RMB. For the RMB exposed to water, VMD performed better and gave limited results in terms of fingerprint development, which could serve as a reference for actual forensic cases.